2022
DOI: 10.1002/jsfa.12096
|View full text |Cite
|
Sign up to set email alerts
|

Developing an innovative raw wheat Qu inoculated with Saccharopolyspora and its application in Huangjiu

Abstract: BACKGROUND Mechanized Huangjiu is a stable product, is not subject to seasonal production restrictions, and markedly reduces labor intensity compared to traditional manual Huangjiu. However, the bitterness of mechanized Huangjiu impedes its further development. RESULTS Based on process optimization, when the fermentation temperature was 45 °C and the fermentation time was 122 h, the inoculation amount of Saccharopolyspora was 5%, the amount of added water was 26%, and the glucoamylase and amylase activities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Thermoascus was positively correlated with Melanoidin, 2-Methoxyphenol, 3-Isopropyl-2,5dimethylpyrazine, 2-Ethyl-6-methylpyrazine, 3-Phenylfuran and Phenol. According to the previous research [29], Aspergillus [30], Monascus [31,32], Byssochlamys, Thermomyces [33], Thermoascus [34], Saccharopolyspora [35,36], and Kroppenstedtia are important functional microorganisms in sauce-flavor Daqu. Although Maillard reaction does not require the participation of microorganisms, these functional microorganisms in BQ, YQ, and WQ participated in the degradation of macromolecular carbohydrates and proteins during Daqu fermentation, which provided a large number of precursors for the Maillard reaction.…”
Section: Composition Of the Microbial Community In Three Kinds Of Daqumentioning
confidence: 97%
“…Thermoascus was positively correlated with Melanoidin, 2-Methoxyphenol, 3-Isopropyl-2,5dimethylpyrazine, 2-Ethyl-6-methylpyrazine, 3-Phenylfuran and Phenol. According to the previous research [29], Aspergillus [30], Monascus [31,32], Byssochlamys, Thermomyces [33], Thermoascus [34], Saccharopolyspora [35,36], and Kroppenstedtia are important functional microorganisms in sauce-flavor Daqu. Although Maillard reaction does not require the participation of microorganisms, these functional microorganisms in BQ, YQ, and WQ participated in the degradation of macromolecular carbohydrates and proteins during Daqu fermentation, which provided a large number of precursors for the Maillard reaction.…”
Section: Composition Of the Microbial Community In Three Kinds Of Daqumentioning
confidence: 97%
“…The raw wheat qu inoculated with S. rosea A22 was prepared by the previous methods ( Ma et al, 2022 ). Briefly, the activated S. rosea A22 seed solution was mixed with water to adjust the bacterial concentration to 10 6 CFU/ml, then the bacterial suspension was added to the crushed wheat at 25–26% (v/m), stirred well and transferred to the fermentation room for 120 h at 45°C.…”
Section: Methodsmentioning
confidence: 99%
“…Several large-scale studies have revealed the diverse biosynthetic potential of various genera like Streptomyces (70,71), Amycolatopsis (17), Salinispora (72), and others. In this study, we selected the Saccharopolyspora genus to demonstrate BGCFlow because of the following: i) many secondary metabolites like erythromycin, spinosyn, and others produced by Saccharopolyspora strains are of great importance to the medicinal (erythromycin), agriculture (spinosyn), and food industry, for example in Chinese liquors (73)(74)(75)(76)(77), ii) there are no comprehensive studies on genome mining across this underexplored genus (73,78), iii) the size of the dataset was sufficiently large for demonstrating all the steps of the BGCFlow.…”
Section: Saccharopolyspora Sppmentioning
confidence: 99%